Economic appraisal of a co-operative mill and a private sugar mill in Punjab -a comparative study - Japbir Kaur; Lavleen Kaur; Sangeet Ranguwal; Parul Barwal (Journal of Sugarcane Research)
The  present  study  was  conducted  in Amritsar  district  of  Punjab  with  the  objectives  to  examine  the  physical  and  ﬁnancial performance of  sugar industry in cooperative vis-a-vis private sector. Secondary data were collected from selected sugar mills and Punjab State Federation Cooperative sugar Mills from 2012-13 to 2021-22. Relative comparison on the physical performance of the two sugar mills viz., Ajnala co-operative sugar mill and Rana sugar mill were made in respect of  four parameters viz total sugar crushed, sugar recovery, total sugar production and total molasses produced. It was observed that for both the mills, rate of  growth was  signiﬁcant  for  all  four  physical  parameters  but  average  sugarcane  crushed,  recovery  percentage,  sugar  production  and molasses production was much higher for privately owned Rana sugar mill in comparison to Ajnala cooperative sugar mill for the study period. Except for total sugarcane crushed, the extent of  instability in the other three parameters of physical performance was large for Rana Sugar mill vis a vis Ajnala cooperative sugar mill. Moreover, the diﬀerent types of proﬁt margin ratios for the Ajnala cooperative sugar mill were negative, whereas such ratios for the Rana Sugar mill were positive.  The physical and ﬁnancial parameters of co-operative and private sugar mills clearly indicated the fact that private sugar mill is performing better than cooperative sugar mill. The average cane crushed for Rana Sugar Mill was 187.85 lakh qtl while for Ajnala cooperative sugar mill it was 19.70 lakh quintals.  It was due to higher mill capacity, longer duration of crushing and more cane availability with Rana Sugar mill.  To increase crushing capacity of  the co-operative mills timely payment to cane farmers should be made and latest machinery in sugar mills should be used. Recovery of sugar was only 8.38 per cent for Ajnala co-operative mill whereas it was 10.29 per cent for Rana sugar mill. It should be increased on the line with private sugar mill through upgradation of technology in cooperative sugar mills.